Analysis of Legal Liability for Parents for the Actions of Children Who Work on Their Own Accord - Nurul Azizah Siregar; Syaiful Asmi Hasibuan; Fitria Ramadhani Siregar (Budapest International Research and Critics University, 2022)
The legal arrangements in Indonesian that address the issue of child labor protection are very clear, Law No. 35 of 2014 concerning child protection, it is emphasized that the organizers of child protection fall on parents, families, communities, governments and the state. The first burden in implementing the protection of children lies with the parents. The legal responsibility of parents, family, community, goverment, state to children is to provide legal protection, one from of legal protection it self is to provide legal certainly, to prevent discrimination, especially in the world of child labor, where some employers employ children. Parents and guardians must play an active role in protecting their children , who are forcec to work for the needs of the family, their rights as children must be fulfilled, namely the right to grow and develop in accordance with human rights, both physically, mentally and socially. Children as the nation's off spring must be protected from all forms of inhumane treatment, which can damage theiar physical, mental and moral values. The purpose of writing scientific journals is to better understand the extent to which parents are legally responsible for the actions of children who work on their own accord in the scientific journals research using a normative method with a conceptual approach. And using legal sources, legal materials in the form of primary, secondary and tertiary legal materials.